Efeito do pré-tratamento ácido diluído na formação de pseudo-lignina em palha de cana-de-açúcar e sacarificação enzimática - Martins, Júlia Ribeiro [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Sugarcane is widely grown, mainly in Brazil, due to its great economic value, as a source of sugar and for ethanol production. Cellulose present in the straw of sugarcane presents potential for the generation of products of outstanding economic importance. The straw consists of the tip and leaves of the sugarcane plant, with high potential for the generation of high value-added products, since that about 30% of the total energy of the plant is contained in this material. The straw is becoming a new abundant residue, studied for its use, such as its conversion into bioethanol, a process in which the recalcitrance of the material needs an application of pre-treatment. In the diluted acid pre-treatment, sugar and lignin-degradation products are generated, which are inhibitors in the enzymatic hydrolysis and fermentation process. In order to improve the effectiveness of pre-treatments and increase the productivity of second-generation ethanol, pretreatment conditions should be controlled. The sugarcane straw was used in pre-treatments with diluted sulfuric acid carried out in stainless steel reactors with an operational volume of 50 mL. The material was subjected to different operating conditions, such as reaction time (10 to 60 minutes), temperature (120 to 180 °C) and acid concentration (2 to 20%, m/m acid mass per mass of material), to evaluate the released sugars and the formation of lignin and pseudo-lignin (lignin condensed with sugar degradation products). The results indicate that very extreme acid pretreatment conditions (60 minutes pretreatment at 180°C and 20% acid) resulted in the degradation of the cellulosic fraction, with a 56.17% reduction in relation to the in natura biomass, which explains the decrease in glucose yield after enzymatic hydrolysis, since these conditions had one of the lowest yields (1.49%). In addition, there was an increase on lignin content in all samples after diluted acid pretreatment, while a reduction in...

A cana-de-açúcar é uma gramínea amplamente cultivada, principalmente no Brasil, graças ao seu grande valor econômico como matéria-prima para produção de açúcar e etanol. A celulose existente em outras partes da biomassa da cana-de-açúcar, como a palha, apresenta também potencial para geração de produtos de destaque econômico. Para o seu aproveitamento, e sua conversão em bioetanol, é necessária a aplicação de pré-tratamentos em virtude de sua recalcitrância. No pré-tratamento ácido diluído (H2SO4) ocorre a formação de produtos de degradação de açúcares e lignina, que são inibidores na hidrólise enzimática e processo fermentativo, podendo ocorrer a condensação entre esses compostos e precipitação sobre a fibra de celulose, formando a pseudo-lignina. Assim, visando melhorar a efetividade dos pré-tratamentos e aumentar a produtividade de etanol de segunda geração, é possível controlar condições do pré-tratamento, como temperatura, tempo de reação e concentração de ácido, com o objetivo de minimizar a formação desses produtos de degradação. Neste estudo, utilizou-se a palha da cana-de-açúcar em pré-tratamentos com ácido sulfúrico diluído realizados em reatores de aço inoxidável com volume operacional de 50 mL. O material foi submetido a diferentes condições operacionais, como tempo de reação (10 a 60 min), temperatura (120 a 180°C) e concentração de ácido (2 a 20 %, m/m massa de ácido por massa de material). Os resultados obtidos indicam que condições muito extremas de pré-tratamento ácido (60 minutos de pré-tratamento, a 180ºC e 20% de ácido) levaram à degradação da fração celulósica, com uma redução de 56,17% em relação à biomassa in natura, o que pode explicar a diminuição do rendimento de glicose após a hidrólise enzimática, já qua tais condições apresentaram um dos menores rendimentos (1,49%). Além disso, houve aumento do teor de lignina em todas...
Keywords: Cana-de-açúcar; Biomassa; Lignina; Etanol celulósico; Enzimas; Ácido sulfúrico; Bioetanol; Palha